2023
DOI: 10.2174/1871526523666230601090905
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Face Masks in Preventing COVID-19 Transmission: A Systematic Review

Abstract: Introduction: Since the beginning of the COVID-19 pandemic, face masks have been among the cornerstones of COVID-19 prevention. Therefore, evaluating their preventive effects against COVID-19 is crucial. This review aimed to systematically search for the systematic review articles that explored the role of various types of face masks in preventing COVID-19. Methods: We browsed the keywords of this study in the online databases of Scopus, Web of Science, PubMed, and Cochrane on 10th January 2023 and retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Wearing a face mask have a beneficial effect in the prevention of respiratory infections, as also observed in recent COVID-19 pandemic [132]. To have the best prevention it is very important to have a comfortable mask that fits well [133].…”
Section: The Sex Of the Human Respiratory Systemmentioning
confidence: 99%
“…Wearing a face mask have a beneficial effect in the prevention of respiratory infections, as also observed in recent COVID-19 pandemic [132]. To have the best prevention it is very important to have a comfortable mask that fits well [133].…”
Section: The Sex Of the Human Respiratory Systemmentioning
confidence: 99%
“…The research by Halpin also suggested that consistent management of chronic respiratory diseases may correlate with a reduced incidence of COVID-19, 21 though this perspective might overlook the preventive benefits of measures like mask-wearing against viruses, bacteria, and harmful particles during the pandemic. 33 In investigations pertaining to individuals afflicted by COVID-19 infection, the elderly patient demographic displayed elevated rates of both morbidity and mortality. 34,35 Initial examinations conducted during the early phase of the COVID-19 outbreak revealed that among all age brackets, the mortality rate was most pronounced among elderly patients.…”
Section: Dovepressmentioning
confidence: 99%